Growth characteristics and root tensile strength’s variability in selected potential shrub species for slope bio-engineering applications - Mohamad Edri Aznan; Zulfahmi Ali Rahman; Siti Norhafizah Tarmidzi; Wan Mohd Razi Idris; Tukimat Lihan; Aeslina Abdul Kadir (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysia’s tropical climate, alternating wet and dry conditions, and high rainfall contribute to soil erosion issues and landslide risk. Soil bioengineering techniques are among the approaches that can be adopted to tackle these issues and reinforce hillslopes. However, selecting appropriate species for bioengineering applications is crucial. Besides the growth of selected plant species, the root tensile strength also plays an important role in soil structure improvement. This research investigated the growth and root characteristics of four potential shrub species namely Strobilanthes crispa (SC), Tabernaemontana divaricata (TD), Pseuderanthemum carruthersii (PC), and Hibiscus rosa-sinensis (HR) as a plant bioengineering material by determining their root tensile force and stress after six months of growth. The soil medium for plant propagation was prepared using a 3:1:1:1 ratio of soil, sand, organic materials, and chicken manure and used for planting the shrub species for 6 months of monitoring. The results show that SC and HR species exhibit superior growth performance in most variables. Root diameter influences mechanical properties of tensile force and stress which can be best presented by power-law equation. TD species has the strongest root for tensile stress, followed by species HR, PC, and SC. All the selected species have potential as biological material in terms of growth performance and root tensile strength. However, further study is essential to evaluate the survivability and root tensile strength of the selected shrubs when implemented on real slopes. This would offer genuine insights into the specific characteristics of their root systems under practical conditions.